Implementasi Kebijakan Peraturan Daerah (PERDA) Kabupaten Wonogiri No. 6 Tahun 2021 Tentang Pembangunan Infrastruktur di Kelurahan Giriwoyo Kecamatan Giriwoyo Kabupaten Wonogiri - Mahastu, Yuan Isha; Suranto, Joko; Suhita, Damayanti (Solidaritas, 2024)
Infrastructure development plays a crucial role in a region, especially in rural areas. It offers numerous benefits such as improving the local economy, the well-being of the community, and, most importantly, eradicating poverty on the path to Indonesia's progress. This research aims to describe the implementation of Regional Regulation No. 6 of 2021 regarding Infrastructure Development in the Giriwoyo Village, Giriwoyo District, Wonogiri Regency. In this study, the researcher employed a qualitative descriptive method based on Edward III's theory (1980:1) with indicators: sommunication, resources, disposition, and bureaucratic structure. Data collection methods included observation, interviews, and documentation. The research results indicate that the implementation of Regional Regulation No. 6 of 2021 on Infrastructure Development in Giriwoyo Village, Giriwoyo District, Wonogiri Regency, can be considered relatively good based on these four indicators. However, it is unfortunate that, during interviews, some community members still did not have a clear understanding of Regional Regulation No. 21 of 2019, which serves as the foundation for implementing infrastructure development policies in Giriwoyo Village. Therefore, it is recommended that the local government in the area be more detailed in their efforts to disseminate information about these programs to the community to ensure a better understanding. Keywords: Policy Implementation, Infrastructure Development.